Den unge Grundtvig som litteraturteoretiker - Aarnes, Sigurd Aa. (Grundtvig-Studier, 1967)
The Young Grundtvig as a Literary Theorist By Sigurd Aa. Aarnes Grundtvig belongs to the class of poets who take an interest in literary theory. He never got down to writing any chief work on the subject, but scattered over the enormous body of his work one finds approaches to a literary theory of a Romantico-idealistic and Christian description. The article analyses a series of comments on poetical theory from the first ten years of Grundtvig’s work (from 1806 to c. 1817). The two great events of Grundtvig’s life during these years are his Romantic crisis as a private tutor at Egeløkke in the island of Langeland, 1805-06, and his Christian crisis in December 1810. These crises were decisive also as regards his poetics. Up to the Romantic turning-point Grundtvig the poet and literary theorist is a 17. century imitator. A completely different view of poetry is revealed, however, in some well-known entries in his diary at Egeløkke, September 9 and 10, 1805: “Poetry is all that bears the stamp of eternity, prose is all that limits its scope to this world” . Thus, Platonically, poetry is considered a reflection of the world of ideas. Poetry is a specific attitude towards (and connection with) “ eternity” , creation viewed sub specie aetemitatis. Grundtvig was to regard poetry forever after in this idealistic and Platonic “ light from above” (“ overlys” ). When he experiences his conversion to a strict Lutheran orthodoxy in December 1810, Grundtvig finds himself, both as a poet and a literary theorist, in an altered situation. His problem now consists in making his poetry legitimate to his Christian conscience. His Romantic philosophy of art will have to fit in with a theological scheme of reference. To ensure this he has to make use of such infrequent points of contact with a philosophy of art as can be found in the Bible. The outlook of the newly converted Grundtvig is well illustrated by his preface to the Norse mythological drama “Optrin af Norners og Asers Kamp” from September 1811. He connects his poetics with theological concepts in three ways: 1. Poetry is “ the true remnant of the image of God which we have lost” (imago dei). 2. Poetry is— like the revelation of God in history and nature—part of the natural revelation. 3. Norse mythology and poetry make up the Old Testament of the Scandinavians. Like the Old Testament prophets the Norse scalds were inspired: They had visions and rendered the vision in writing. These two functions—vision and “ action according to vision” (“Virken efter Syn” )—are always common to the prophet and the poet. Eternal truth can be communicated to man only metaphorically. Therefore— as emphasized especially in “Om det østerlandske Billedsprog” , a sermon from the middle of the 1820’s—God linked the divine revelation in the Bible with the language of poetry, the language of metaphor, and thus made this language holy.